0459 Is It Having a Baby or Me? Differentiating Insomnia Disorder and Sleep Disruption from Pregnancy to 2 Years Postpartum. (27th May 2020) - Quin, N; Lee, J; Pinnington, D M; Shen, L; Manber, R; Bei, B
Abstract: Introduction: Insomnia Disorder (Insomnia) diagnosis requires sleep complaints to persist despite "sleep-conducive conditions and adequate sleep opportunity". Women experience significant sleep disruption during pregnancy and postpartum periods due to physiological changes and night-time infant care, but not all women with sleep complaints meet Insomnia criteria. This study examined sleep and mental health correlates of Insomnia Disorder and sleep complaints in the context of a randomised controlled trial for improving maternal sleep. Methods: 163 generally healthy first-time mothers (age M±SD=33.4±3.5) with singleton pregnancy repeated the following assessments at 28-30 and 35-36 weeks' gestation, and 1.5, 3, 6, 12, and 24 months postpartum: the Insomnia module of the Duke Structured Interview for Sleep Disorders, PROMIS Sleep-Related Impairment, Depression, and Anxiety Short Forms. We compared clinical features when DSM-5 Insomnia criteria (less the 3-month criteria) were (1) met (Insomnia), (2) not met only because of the sleep condition/opportunity criteria (Sleep Disruption), and (3) not met due to low symptom/distress (Low Complaint). Results: 944 interviews and 1009 questionnaire were collected across 7 time-points. Proportions of women meeting Insomnia criteria were 16.0% and 19.8% during early and late third trimester, and ranged 5.3-11.7% during the 5 postpartum time-points. If the sleep condition/opportunity criteria were not considered, rates of "Insomnia" would have been 2-4 times higher at 21.4-40.4% across all time-points. Mixed effects models, controlling for intervention allocation, showed that compared with Insomnia, Sleep Disruption had comparable depression (p=.68) and anxiety (p=.23), and somewhat lower sleep-related impairment (p=.06). These symptoms were lowest for Low Complaint. Conclusion: Both Insomnia and Sleep Disruption were associated with significant daytime impairment, depression, and anxiety. Assessing sleep complaints without considering sleep condition/opportunity can result in over-diagnosis of perinatal Insomnia in these women with primarily sleep disruption; these women may have limited benefits from Insomnia-specific treatment. Interventions for maternal sleep should carefully differentiate between Insomnia and other sleep concerns (e.g., sleep disruption/opportunity, sleepiness/fatigue) and appropriately address each. Support: Australasian Sleep Association, Monash University, Royal Women's Hospital Foundation. National Health and Medical Research Council, Department of Education and Training.